Effects of 6-Gingerol Supplementation in Cryopreservation on Human Sperm Parameters, DNA Fragmentation, and Apoptosis Incidence - Zekri, Shadi; Bahiraei, Roya; Ghezelayagh, Zeinab; Maghami, Parvaneh; Shahverdi, Abdolhossein; Sabbagian, Marjan; Ebrahimi, Bita (Urology Journal, 2025)
Purpose: Sperm cryopreservation is a valuable method for fertility preservation in men who suffer from oligozoospermia and cancer. The increase in oxidative stress during this process negatively affects sperm viability, membrane fluidity, and function. Supplementation of antioxidants to the cryopreservation medium can reduce these negative effects. This study investigated the effects of 6-gingerol as a natural antioxidant during human sperm cryopreservation on different sperm parameters, DNA fragmentation, and apoptosis. Materials and Methods: In this experimental study, semen samples were obtained from 42 normozoospermic men referred to the Royan Institute. The samples were randomly divided into fresh, control (cryopreservation), and gingerol (cryopreservation with 6-gingerol) groups. Sperm evaluations were conducted before and after cryopreservation. Sperm parameters, DNA fragmentation index (DFI), caspase-3 activity, reactive oxygen species (ROS) levels, malondialdehyde (MDA) concentration, and total antioxidant capacity (TAC) levels were assessed. Results: Use of 6-gingerol in the cryopreservation medium resulted in recovery of a significantly higher proportion of viable sperm post-cryopreservation compared with the control group (64.1 ± 1.3% vs 56.4 ± 1.3%; P = 0.000). ROS levels were significantly lower (P = 0.000), and the percentage of sperm with intact membrane potential was significantly higher (P = 0.000) in the gingerol group (26.1 ± 0.1 RLU/s; 63.5 ± 1.4%) compared with the control group (32.1 ± 0.7 RLU/s; 53.3 ± 1.5%). Active caspase-3 (P = 0.007) and DFI (P = 0.008) were lower in the gingerol group (47.3 ± 3.6%; 37.9 ± 1.3%, respectively) compared with the control group (60.5 ± 3.6%; 42.1 ± 0.1%, respectively), though the differences for caspase-3 and DFI did not reach statistical significance where indicated by the authors. Conclusion: Supplementation of the sperm cryopreservation medium with 6-gingerol could improve sperm quality and function and positively affect the degree of apoptosis during sperm freezing.